Corporate venture capital. Synergy of corporate venture fund and corporate business incubator - S. V. ALEKSA (Стратегии бизнеса, 2017)
Today in the world where the frequency of occurrence of new technologies reaches its maximum, the rate of reaction and flexibility of the large enterprises in all markets in any location is very important. Every industry is rapidly developing, creating new products and services where development drivers are not multi-billion corporations, but small startups that tries to create a unique and innovative product that will be able to compete in highly competitive markets or can create its own "blue ocean". The main task of the "giants" of the market in such situation, not to compete with a promising company, but to use these opportunities for the benefit of strategic or financial goals.